"France's (Kinder, Gentler) Extremist": Marine Le Pen, Intersectionality, and Media Framing of Female Populist Radical Right Leaders. Issue 2 (June 2020) - Snipes, Alexandra; Mudde, Cas
Abstract: Although the populist radical right is generally seen as a particularly masculine and misogynist phenomenon, several of its parties have female leaders. The most prominent is Marine Le Pen, president of the French National Rally (formerly the National Front) and unofficial leader of the European populist radical right. Using insights from intersectionality theory, we posit that Marine Le Pen, as a female populist radical right politician, faces qualitatively different media coverage than both her female and her radical right counterparts. In this study, we analyze her media framing in two French ( Le Figaro and Le Monde ) and two U.S. ( New York Times and Wall Street Journal ) newspapers, focusing on the application of gender and populist radical right frames. We find that the "harder" populist radical right frame dominates the "softer" gender frame in all four newspapers, but, paradoxically, the combination of the two frames leads to overall less biased coverage of Marine Le Pen compared with both other female and other populist radical right politicians. In the conclusion, we discuss some of the consequences of the findings for the broader study of female politicians, most notably, theories of intersectionality and the double bind for women in leadership.